2019
DOI: 10.7717/peerj.7961
|View full text |Cite
|
Sign up to set email alerts
|

The effect of habitat changes along the urbanization gradient for breeding birds: an example from the Xiong’an New Area

Abstract: BackgroundBecause of its status as an ecocivilization pilot city, fundamental research on spatial distribution patterns and impact factors of the avian community within the Xiong’an New Area is necessary for future ecological planning and mitigation of negative impacts from future urbanization. Gradient research within small cities can provide important information for the development of urbanization gradient patterns of avian communities.MethodsA total of 30 sample points within the urbanization gradient were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 120 publications
1
8
0
Order By: Relevance
“…A recent study by [88] showed that higher bird congregations in the cities are associated with seasons and specific diet especially in spring and winter. In our study, the number of human-bird conflicts was more in spring and summer, which might be associated with the breeding season of birds determined by the temperate environment in Krakow area.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by [88] showed that higher bird congregations in the cities are associated with seasons and specific diet especially in spring and winter. In our study, the number of human-bird conflicts was more in spring and summer, which might be associated with the breeding season of birds determined by the temperate environment in Krakow area.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling sites were located in the Xiong'an New Area (38 (Li et al, 2020). The Xiong'an New Area has a warm temperate continental monsoon-type climate with four seasons and significant differences between cold, warm, and humid periods and has an annual average temperature of 12.1 • C, frostfree period of 173 days, and an average yearly precipitation of 560 mm (Xu et al, 2018;Xie et al, 2019). The Millennium Xiulin area was launched in November 2017 with the aim of creating an appealing ecological environment and constructing a new and impressive ecological city.…”
Section: Sampling Site and Sample Collectionmentioning
confidence: 99%
“…The extraction was repeated two times to obtain sufficient DNA yield. The concentration and purity of the DNA were measured using a NanoDrop 2000 spectrophotometer (Thermo Fisher Scientific, Wilmington, DE, USA), and the integrity of the DNA was subsequently examined by agarose gel electrophoresis with 1% agarose gels (Cregger et al, 2018;Wang et al, 2019).…”
Section: Dna Extractionmentioning
confidence: 99%
“…The endeavor explores a new model of optimized development in densely populated areas and promotes the integration of the Beijing-Tianjin-Hebei city-region [19]. In light of the "big city malaise" (e.g., traffic and environmental problems) typical of previous urbanization, policymakers have made ecological and green development the top priority in the creation of XNA [20].…”
Section: Xiongan New Areamentioning
confidence: 99%